(untitled) (Asian Journal of Medical and Biological Research, 2020)
The emergent medicinal plant Gynura procumbens to the greatest extent familiar in Bangladesh, India, Thailand and Southeast Asia. The plant usually used as a traditional medicine for the treatment of various diseases along with diabetes mellitus. The present investigation was try to display screen qualitative and quantitative phytochemical compositions of ethanol extract of Gynura procumbens leaves as an instance soluble sugar, total amino acids, protein, chlorophyll, flavonoids, tannins, phenol as standard techniques and antioxidant activity as DPPH radical scavenging assay and compare the antibacterial activity by using agar well diffusion method. Qualitative evaluation exhibit present of most of the phytochemicals and quantitative evaluation revealed primary chemical constituents consisting of amino acids (16.34 mg/g), soluble sugar (1.81 mg/g), total chlorophyll (0.52 mg/g), chlorophyll-a (0.34 mg/g), chlorophyll-b (0.145 mg/g) and lowest amount of phytochemical turned into protein (0.12 mg/g). Secondary chemical constituents together with flavonoids (30.32 mg/g), phenols (10.17 mg/g) and tannin (0.96 mg/g). The observation also confirmed great antioxidant activity in a concentration dependent manner via the scavenging of 1, 1-diphenyl-1-picrylhydrazyl radical (DPPH). Result confirmed that, the studied sample has high antioxidant efficacy. The antibacterial interest confirmed as negative effects in all bacteria’s tested. These results advise that Gynura extract is a good herbal supply of bioactive compounds. Asian J. Med. Biol. Res. June 2020, 6(2): 187-195